2008
DOI: 10.1093/ndt/gfn209
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation in adults with Henoch-Schonlein purpura: long-term outcome

Abstract: Long-term patient and allograft survival of HSP patients was good. However, 42% of HSP patients, particularly those with necrotizing/crescentic glomerulonephritis of the native kidneys, developed a recurrence of HSP nephritis that eventually caused the loss of the graft function in half of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…They showed a graft-survival rate of 95% at 5 years and 87.7% at 10 years for the HSP group, which was not statistically different from their control populations (P ϭ 0.209 for the 10 years survival rate comparison). Similarly Moroni et al (21) reported data on 19 HSP patients requiring renal transplantation over a period of 27 years. After matching 1:2 with controls for age range, gender, and donor source, they found equivalent graft survival with 15 years of follow-up; the death-censored graft-survival rate in the HSP group was 75% at 10 years compared with 70% in the control group (21).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…They showed a graft-survival rate of 95% at 5 years and 87.7% at 10 years for the HSP group, which was not statistically different from their control populations (P ϭ 0.209 for the 10 years survival rate comparison). Similarly Moroni et al (21) reported data on 19 HSP patients requiring renal transplantation over a period of 27 years. After matching 1:2 with controls for age range, gender, and donor source, they found equivalent graft survival with 15 years of follow-up; the death-censored graft-survival rate in the HSP group was 75% at 10 years compared with 70% in the control group (21).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly Moroni et al (21) reported data on 19 HSP patients requiring renal transplantation over a period of 27 years. After matching 1:2 with controls for age range, gender, and donor source, they found equivalent graft survival with 15 years of follow-up; the death-censored graft-survival rate in the HSP group was 75% at 10 years compared with 70% in the control group (21). The remaining four smaller case series reported 5-year allograft survival ranging from 70% to 89% (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In HSPN, IgA deposition can be found not only in the kidney, but also in other organs, such as the skin. IgA deposition recurs in some patients after renal transplantation [26,27], and after the transplantation of kidneys with mild forms of IgAN, immune complex deposition and nephritic changes decrease and disappear [28], rendering an extrarenal source of IgA very likely. To date, the pathophysiology of IgAN and HSPN seems to be identical, with only quantitative differences, possibly accounting for the different clinical presentation with more acute signs of nephritis in HSPN and a more insidious onset in IgA nephropathy.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…However, there is a reported 42% recurrence rate, with loss of the graft in half of those patients. 15 Our patient's clinical course highlights the problems associated with evaluating and treating HSP. He has had an extraordinarily labile course with multiple exacerbations and remissions.…”
Section: Discussionmentioning
confidence: 92%